THE EFFECTIVENESS OF USING PROBLEM-BASED LEARNING (PBL) LEARNING MODEL TOWARDS CRITICAL THINKING STUDENTS OF CLASS VII SMP - Dwi Kusmiati; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The teacher still does learning so that it has not allowed students to develop independence through finding and thought processes. Therefore, critical thinking becomes very less. The purpose of this study is to find out the values of students' critical thinking learning using the PBL learning model and direct learning model and compare the effectiveness of PBL learning model and direct learning model to critical thinking skills of students of Class VII of State Junior High School 3 Kasihan (SMP Negeri 3 Kasihan) Bantul in Academic Year of 2017/2018. The population of this study is all of the students of class VII. The samples were taken by using a random sampling technique. As the experiment class was Class VII and as the control class was Class VII A. The data collecting of this study using the essay test. The data collecting instrument of this study by using the validity test and reliability test. The data analysis technique used a prerequisite analysis test. There are normality test and homogeneity test, and hypothesis test using a t-test. The result of a significant level of 5% and df =60 showed that: (1) there was a different ability between students' critical thinking, which used the PBL learning model with a direct learning model. The value of  = 2,682884 shows it>  = 2,0003 and (2) the PBL learning model more effective than the direct learning model toward students' critical thinking ability. This research showed that the  = 2,682884 >  = 1,6706.